2014
DOI: 10.1111/ans.12640
|View full text |Cite
|
Sign up to set email alerts
|

Total pancreatectomy for the treatment of pancreatic neoplasms

Abstract: TP should be considered in selective cases for treatment of pancreatic neoplasm if it allows complete clearance. The procedure does not appear to be associated with significant increases in serious complications compared with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…The rates of other clinically significant complications were similar between the 2 groups [41] . While 3 reports showed no differences in morbidity between TP and PD [4,9,42] , 3 showed significant differences between these procedures [16,40,41] . While the perioperative mortality rates for TP have decreased in recent years, perioperative morbidity after TP did not decrease significantly (1970-1989: 70.0%; 1990-1999: 70.3%; 2000-2007: 66.0%; p = 1.0) [40] .…”
Section: The Comparison Of Tp and Pdmentioning
confidence: 64%
See 3 more Smart Citations
“…The rates of other clinically significant complications were similar between the 2 groups [41] . While 3 reports showed no differences in morbidity between TP and PD [4,9,42] , 3 showed significant differences between these procedures [16,40,41] . While the perioperative mortality rates for TP have decreased in recent years, perioperative morbidity after TP did not decrease significantly (1970-1989: 70.0%; 1990-1999: 70.3%; 2000-2007: 66.0%; p = 1.0) [40] .…”
Section: The Comparison Of Tp and Pdmentioning
confidence: 64%
“…In these papers, the morbidity rates were 31-87% and included delayed gastric emptying, bleeding, infections, and problems with glycemic control. Nikfarjam et al [41] reported a higher morbidity rate with a significantly greater number of grade-1 complications according to the Clavien-Dindo classification system, reflecting a high postoperative hypoglycemia rate. The rates of other clinically significant complications were similar between the 2 groups [41] .…”
Section: The Comparison Of Tp and Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 The complications associated with diabetes involve numerous other disorders such as cardiovascular, developmental, immune, metabolic, neurodegenerative, obesity, renal and vision. [15][16][17][18][19] Both of the two major forms of diabetes, type 1, an autoimmune disease 20,21 and type 2, a metabolic disorder, [22][23][24][25] require novel approaches to early diagnosis and therapy. [26][27][28][29] Notwithstanding the availability of several classes of anti-diabetic drugs, it is often difficult to maintain long-term glycemic control and many current agents have treatment-limiting side effects.…”
mentioning
confidence: 99%